PENINGKATAN HASIL BELAJAR SISWA KELAS IV SD NEGERI KARANGWUNI 03 DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - SRI MULYANI (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2021)
This research aims to implement a cooperative learning model of STAD type to improve the results of mathematics learning grade IV SD Karangwuni 3, which is under KKM. This method is also used to provide the innovation of learning methods in these subjects so that students can play an active role in the KBM process. This research is a class action study using three cycles. Based on the results of research and data analysis can be concluded through cooperative learning methods type STAD can improve students' learning outcomes in cognitive, affective and psychomotor aspects in each cycle. In cycle 1 shows not yet maximum achievement, percentage of success (completeness) of students from cognitive scores 60%, Affective scores 70%, and psychomotor 70%. In cycle II, presentation increased students' overall cognitive, affective, and psychomotor scores by 70% with an average score of 81.3 in all three aspects. Then for the third cycle shows quite significant results with an average value of 87.0, and the completeness level is 90-100%.